Green Economy in the Map of Science: Bibliometric Analysis of Publication Patterns and Collaboration - Ronal Satria; Husni Shabri (Imara: Jurnal Riset Ekonomi Islam, 2025)
Background. Research on the Green Economy has grown significantly in recent years. However, to fully understand the direction and trends of this field, a comprehensive analysis of existing scientific publications is necessary. One effective approach is bibliometric analysis, which enables the mapping of developments and thematic expansions in Green Economy research. Purpose. This study aims to conduct a bibliometric analysis using VOSviewer to explore the development and expansion of Green Economy research themes and to predict potential future research directions.Method. This research adopts a descriptive quantitative approach. Data were collected from the Scopus database using the keyword ÔÇ£Green EconomyÔÇØ for the period 2015ÔÇô2024, resulting in 200 relevant articles. The data were analyzed descriptively, processed with VOSviewer for bibliometric visualization, and reviewed through literature analysis to identify trends and patterns within the topic.Results. The findings show a significant annual increase in publications on the Green Economy from 2015 to 2024. The analysis using VOSviewer revealed a total of 700 citations related to this topic. Moreover, the bibliometric mapping indicated an expansion of research themes and identified several underexplored areas within the field of Green Economy.Conclusion. This study provides important insights into the development of Green Economy research. The findings help to identify well-researched areas as well as topics that have received limited attention, offering a foundation for future research in this evolving field